"Looking Forward": a qualitative evaluation of a physical activity program for middle-aged and older adults with serious mental illness. (28th December 2020) - Dobbins, Sarah; Hubbard, Erin; Leutwyler, Heather
ABSTRACT: Objectives: Older adults with serious mental illness (SMI) often have poor physical health in addition to serious mental health issues. Sustained engagement in a group physical activity program may provide necessary physical and mental health benefits. The purpose of this report is to describe participants' feedback about a video game-based group physical activity program using the Kinect for Xbox 360 game system (Microsoft, Redmond, WA). In particular, we wanted to understand what worked about the program, what was not ideal, and how it impacted their lives. Design: Semi-structured interviews were collected and analyzed with grounded theory methodology. Setting: Mental health facility. Participants: Sixteen older adults with SMI. Measurements: Participants played an active video game for 50-minute sessions, three times a week for 10 weeks. Qualitative interviews were conducted with 16 participants upon completion of the program. Results: Participants expressed enthusiasm for the physical activity program, indicating it was an activity that they looked forward to doing. The results of the study provide insight into how the program may be implemented into practice at mental health facilities. Three implementation to practice categories were identified: (1) programmatic considerations, such as when to hold the groups and where; (2) the critical importance of staff involvement; and (3) harnessing patients' interest in the program. Conclusion: Our results suggest that engagement in an intense video game-based group physical activity program has a positive impact on participants' overall health. The group atmosphere, staff involvement, availability of the program at a mental health facility, and health benefits were critical.